A method for preparing an energy-saving corrosion-inhibiting decarbonizing agent
By using the combination of modified N-methyldiethanolamine, activator and corrosion inhibitor in the natural gas decarbonization process, the problems of low absorption rate and high equipment corrosion and regeneration energy consumption in the prior art are solved, and the decarbonization effect of high efficiency, energy saving and corrosion inhibition is achieved.
Patent Information
- Application Number
- CN202411896561.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing natural gas decarbonization process has problems such as low absorption rate, high equipment corrosion and regeneration energy consumption.
The energy-saving corrosion-resistant decarbonizer is prepared by mixing vinyl carbonate, catalyst and anhydrous ethanol after being reacted with methylamine solution to form N-methyldiethanolamine, and modified by 1,3-propanesulfonic acid lactone, combined with activator and corrosion inhibitor.
The absorption rate and absorption amount of carbon dioxide are improved, the regeneration energy consumption and equipment corrosion risks are reduced, and the efficient decarbonization effect is achieved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomass gasification catalysts, and in particular relates to a method for preparing an energy-saving and corrosion-inhibiting decarbonizing agent. Background Art
[0002] During the oil and gas production process, natural gas from underground reservoirs usually contains a certain amount of acidic components such as H2S and CO2, which not only reduces the quality of natural gas, but also corrodes metal pipelines, equipment reactors, etc., affecting the storage, transportation and utilization of natural gas. Therefore, natural gas must be desulfurized and decarbonized to meet national natural gas standards.
[0003] At present, the main decarbonization methods used in industrial production include adsorption, cryogenic distillation, membrane separation, physical absorption and chemical absorption. Among them, chemical absorption has become the mainstream due to its advantages of high absorption efficiency and relatively stable absorbent. Commonly used absorbents include potash, sodium alkali, ammonia water, alcohol amine solution, etc. Large-scale natural gas desulfurization and decarbonization devices at home and abroad are mainly based on alcohol amine solution absorption, such as MDEA method, which has the advantages of continuous operation, large processing capacity, high purification degree and wide adaptability to the concentration range of acidic gas components. However, this decarbonization process has a slow absorption rate for CO2, and the energy consumption of CO2 desorption is high.
[0004] The Chinese patent application document with publication number CN102641653A discloses a process for removing carbon dioxide from vinyl acetate reaction cycle gas, which uses an inorganic activator composed of potassium carbonate and a mixture of one or more of potassium metavanadate, boric acid, selenious acid, antimonic acid, and telluric acid in a certain proportion to prepare a mixed solution to adsorb carbon dioxide from the reaction cycle gas. The inorganic activator used in this method is highly corrosive to the equipment and has insufficient removal accuracy.
[0005] In addition, solid amine adsorbent is a dual advantage of combining solid amine solution and solid adsorbent material, with high efficiency, fast selectivity, low energy consumption characteristics, can be used as a substitute for composite amine liquid potential products. Due to the high reactivity between the loaded amine and CO2, the solid amine adsorbent can efficiently and quickly selectively adsorb CO2, and compared with the amine solution, the CO2 regeneration energy can be greatly reduced. However, the thermal stability of the current solid amine material is poor, and the material pore structure is uneven, so the decarbonization effect is not good. For example, the Chinese patent application document with the publication number CN114522504A discloses a method for removing carbon dioxide from high-purity gas, wherein the high-purity gas is passed into a polyethyleneimine loaded adsorbent for adsorption and removal of carbon dioxide, and the polyethyleneimine loaded adsorbent includes a carrier and a polyethyleneimine loaded on the carrier, and the specific preparation method is: dissolving polyethyleneimine in an organic solvent, then adding a dry carrier, stirring to form a mixture, and drying. This polyethyleneimine loaded adsorbent has a high selectivity and adsorption capacity for CO2, and can remove it to less than 0.5ppm, achieving the effect of deep removal of CO2 impurities. However, its decarbonization effect is limited by the loading amount of polyethyleneimine on the carrier, and the regeneration energy consumption of the decarbonization agent is relatively high.
[0006] In summary, the development of a decarbonizer that combines energy saving, corrosion inhibition and decarbonization has become a necessary choice for the development of the industry. Summary of the invention
[0007] In order to solve the technical problems of low absorption rate, equipment corrosion and high regeneration energy consumption existing in the related art, the purpose of the present invention is to provide a preparation method of an energy-saving and corrosion-inhibiting decarbonizer.
[0008] In order to achieve the above object, the technical solution of the present invention is as follows:
[0009] A method for preparing an energy-saving corrosion-inhibiting decarbonizer comprises the following steps:
[0010] S1: Ethylene carbonate, catalyst and anhydrous ethanol are mixed and added into a reaction kettle, methylamine solution is added dropwise after heating, the mixture is kept warm for reaction, and cooled to obtain a main absorbent solution;
[0011] S2: dissolving 1,3-propane sultone in anhydrous ethanol and mixing them evenly to obtain solution A; then adding the obtained solution A dropwise to the main absorbent solution prepared in step S1 under room temperature and stirring, and reacting at the same temperature to obtain a modified absorbent solution;
[0012] S3: adding an activator, a corrosion inhibitor and boric acid to the modified absorbent solution obtained in step S2, stirring evenly, and obtaining an energy-saving corrosion-inhibiting decarbonizer.
[0013] In the present invention, ethylene carbonate and methylamine are used as basic raw materials to synthesize N-methyldiethanolamine under the action of a catalyst, and then 1,3-propane sultone is used to modify N-methyldiethanolamine. 1,3-propane sultone can combine with water molecules to form a hydration layer, which can effectively isolate hydrocarbon substances in oil and gas without causing hydrocarbon loss, thereby increasing the absorption amount and absorption rate of carbon dioxide by N-methyldiethanolamine, and at the same time, the number of times N-methyldiethanolamine is reused can be increased, solving the technical problem of high regeneration energy consumption. In addition, in the present invention, an activator is added to the energy-saving corrosion-inhibiting decarbonizer, which can effectively increase the absorption rate of carbon dioxide by the decarbonizer and reduce the desorption energy consumption of carbon dioxide; and the addition of the corrosion inhibitor can effectively reduce the corrosion inhibition of metal equipment.
[0014] Furthermore, in step S1, the weight proportions of ethylene carbonate, catalyst and methylamine solution are respectively: 40-50 parts of ethylene carbonate, 5-8 parts of catalyst and 20-30 parts of methylamine solution.
[0015] Furthermore, the catalyst in step S1 is one of strong basic styrene type I anion exchange resin, strong basic styrene type II anion exchange resin and 717 anion exchange resin.
[0016] Furthermore, the mass percentage of the methylamine solution in step S1 is 40%-45%, and the dropping speed of the methylamine solution is 0.32-0.43 mL / min.
[0017] Furthermore, the heating temperature in step S1 is 115-130° C., and the insulation reaction time is 2-2.5 hours.
[0018] Furthermore, the amount of 1,3-propane sultone used in step S2 is 0.8-1.2 times the mass of ethylene carbonate.
[0019] Furthermore, the dropping speed of the solution A in step S2 is 0.5-0.7 mL / min.
[0020] Furthermore, the activator in step S3 is composed of 2-amino-2-methyl-1-propanol and ethanolamine in a mass ratio of 4-8:3-5.
[0021] 2-Amino-2-methyl-1-propanol can greatly reduce the stability of carbamate by steric hindrance effect, thereby increasing the absorption and desorption rate of carbon dioxide and reducing the regeneration heat consumption; while the addition of ethanolamine to the solution will cause the OH in the solution to - As the concentration increases, ethanolamine reacts with carbon dioxide to form carbamate, generating more OH - , thereby promoting the reaction of carbon dioxide and OH -In the present invention, 2-amino-2-methyl-1-propanol and ethanolamine are selected to form an activator, which effectively promotes the absorption of carbon dioxide by the decarbonizing agent and reduces the regeneration energy consumption.
[0022] Furthermore, the corrosion inhibitor in step S3 is composed of N-methyl-1-hexadecylamine and 2-methylbenzothiazole in a mass ratio of 11-14:7-9.
[0023] In the present invention, N-methyl-1-hexadecylamine and 2-methylbenzothiazole are selected to form a corrosion inhibitor, which can form a dense hydrophobic film on the surface of the pipeline to protect the metal surface from corrosion.
[0024] Furthermore, in step S3, the mass fraction of the corrosion inhibitor is 20-25 parts, the mass fraction of the activator is 10-15 parts, and the mass fraction of the boric acid is 10-15 parts.
[0025] Compared with the prior art, the preparation method of the energy-saving corrosion-inhibiting decarbonizer provided by the present invention has the following technical advantages:
[0026] (1) The energy-saving corrosion-inhibiting decarbonizer provided by the present invention uses 1,3-propane sultone to modify N-methyldiethanolamine, effectively improving the absorption rate of carbon dioxide and reducing the regeneration energy consumption;
[0027] (2) The energy-saving corrosion-inhibiting decarbonizer provided by the present invention uses 2-amino-2-methyl-1-propanol and ethanolamine to form an activator, and uses N-methyl-1-hexadecylamine and 2-methylbenzothiazole to form a corrosion inhibitor, which effectively promotes the absorption of carbon dioxide by the decarbonizer and reduces the regeneration energy consumption and corrosion to metal equipment;
[0028] (3) The preparation process of the energy-saving and corrosion-inhibiting decarbonizer provided by the present invention is simple, and the raw materials are readily available, which is conducive to industrial production. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. Those skilled in the art can make various modifications based on the basic idea of the present invention, but as long as they do not deviate from the basic idea of the present invention, they are all within the scope of the present invention.
[0030] Example 1
[0031] A method for preparing an energy-saving corrosion-inhibiting decarbonizer comprises the following steps:
[0032] S1: 40 g of ethylene carbonate, 5 g of strong basic styrene type I anion exchange resin and 60 mL of anhydrous ethanol were mixed and added into a reactor. After heating to 115°C, 20 g of 40% methylamine solution was added dropwise at a rate of 0.32 mL / min. The mixture was kept warm for 2 h and cooled to 25°C to obtain a main absorbent solution.
[0033] S2: 32 g of 1,3-propane sultone was dissolved in 30 mL of anhydrous ethanol, and the mixture was uniformly mixed to obtain a solution A; the obtained solution A was then added dropwise to the main absorbent solution obtained in step S1 at a rate of 0.5 mL / min under room temperature and stirring, and the temperature was maintained at 25° C. for 24 hours to obtain a modified absorbent solution;
[0034] S3: Add 10g of activator, 20g of corrosion inhibitor and 10g of boric acid to the modified absorbent solution obtained in step S2, stir evenly, and obtain an energy-saving corrosion-inhibiting decarbonizer; the activator is composed of 2-amino-2-methyl-1-propanol and ethanolamine in a mass ratio of 4:3; the corrosion inhibitor is composed of N-methyl-1-hexadecylamine and 2-methylbenzothiazole in a mass ratio of 11:7.
[0035] Example 2
[0036] A method for preparing an energy-saving corrosion-inhibiting decarbonizer comprises the following steps:
[0037] S1: 50 g of ethylene carbonate, 8 g of strong basic styrene II type anion exchange resin and 60 mL of anhydrous ethanol were mixed and added into a reactor. After heating to 130°C, 30 g of 45% methylamine solution was added dropwise at a rate of 0.43 mL / min. The mixture was kept warm for 2.5 h and cooled to room temperature to obtain a main absorbent solution.
[0038] S2: Dissolve 60g of 1,3-propane sultone in 30mL of anhydrous ethanol and mix well to obtain solution A; then add the obtained solution A dropwise to the main absorbent solution prepared in step S1 at a rate of 0.7mL / min under room temperature and stirring, keep the temperature at 25°C and react for 24h to obtain a modified absorbent solution;
[0039] S3: Add 15g of activator, 25g of corrosion inhibitor and 15g of boric acid to the modified absorbent solution obtained in step S2, stir evenly, and obtain an energy-saving and corrosion-inhibiting decarbonizer; the activator is composed of 2-amino-2-methyl-1-propanol and ethanolamine in a mass ratio of 8:5; the corrosion inhibitor is composed of N-methyl-1-hexadecylamine and 2-methylbenzothiazole in a mass ratio of 14:9.
[0040] Example 3
[0041] A method for preparing an energy-saving corrosion-inhibiting decarbonizer comprises the following steps:
[0042] S1: 48g of ethylene carbonate, 7g of 717 anion exchange resin and 60mL of anhydrous ethanol were mixed and added into a reactor. After heating to 123°C, 27g of 43% methylamine solution was added dropwise at a rate of 0.39mL / min. The mixture was kept warm for 2.2h and cooled to room temperature to obtain a main absorbent solution.
[0043] S2: Dissolve 48g of 1,3-propane sultone in 30mL of anhydrous ethanol and mix well to obtain solution A; then add the obtained solution A dropwise to the main absorbent solution prepared in step S1 at a rate of 0.6mL / min under room temperature and stirring, keep the temperature at 25°C and react for 24h to obtain a modified absorbent solution;
[0044] S3: Add 13g of activator, 23g of corrosion inhibitor and 13g of boric acid to the modified absorbent solution obtained in step S2, stir evenly, and obtain an energy-saving and corrosion-inhibiting decarbonizer; the activator is composed of 2-amino-2-methyl-1-propanol and ethanolamine in a mass ratio of 7:4; the corrosion inhibitor is composed of N-methyl-1-hexadecylamine and 2-methylbenzothiazole in a mass ratio of 13:8.
[0045] Comparative Example 1
[0046] The preparation method of the energy-saving and corrosion-inhibiting decarbonizer in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that an equal amount of anhydrous ethanol is used instead of 1,3-propane sultone in this comparative example.
[0047] Comparative Example 2
[0048] The preparation method of the energy-saving corrosion-inhibiting decarbonizer in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that an equal amount of alkyl dimethyl sulfopropyl betaine is used instead of 1,3-propane sultone in this comparative example.
[0049] Comparative Example 3
[0050] The preparation method of the energy-saving and corrosion-inhibiting decarbonizer described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that the activators described in this comparative example are all 2-amino-2-methyl-1-propanol.
[0051] Comparative Example 4
[0052] The preparation method of the energy-saving and corrosion-inhibiting decarbonizer in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that the activators in this comparative example are all ethanolamine.
[0053] Comparative Example 5
[0054] The preparation method of the energy-saving and corrosion-inhibiting decarbonizer described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that the activator described in this comparative example is composed of 2-amino-2-methyl-2-propanol and ethanolamine in a mass ratio of 4:7.
[0055] Comparative Example 6
[0056] The preparation method of the energy-saving corrosion-inhibiting decarbonizer described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that the corrosion inhibitors described in this comparative example are all N-methyl-1-hexadecylamine.
[0057] Comparative Example 7
[0058] The preparation method of the energy-saving corrosion-inhibiting decarbonizer described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that the corrosion inhibitors described in this comparative example are all 2-methylbenzothiazole.
[0059] Comparative Example 8
[0060] The preparation method of the energy-saving corrosion-inhibiting decarbonizer described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that the corrosion inhibitor described in this comparative example is composed of N-methyl-1-hexadecylamine and 2-methylbenzothiazole in a mass ratio of 2:13.
[0061] Test example
[0062] In this test example, simulated flue gas was used to test the absorption rate, desorption rate and regeneration energy consumption of the energy-saving corrosion-inhibiting decarbonizers prepared in Examples 1 to 3 and Comparative Examples 1 to 5. The composition of the simulated flue gas is (volume): CO2: 20.25%; O2: 8.27%; H2O: 10.12%; N2: 59.01, CO: 2.35%; trace sulfides and nitrogen oxides.
[0063] Flue gas decarbonization: The flue gas decarbonizer of the present invention is preheated to 50°C through a heat exchanger, sprayed from the top of the absorption tower, and the flue gas is introduced from the bottom of the absorption tower, and the liquid-gas ratio is controlled to be 1.25kg / m 3 , the flue gas decarbonizer contacts the gas containing carbon dioxide in reverse, the purified gas is discharged into the atmosphere through the top of the tower, and the decarbonizer that absorbs CO2 is called rich liquid, which enters the rich liquid tank from the bottom of the tower. The composition of the gas discharged from the top of the tower is detected by an enhanced flue gas analyzer (Germany, model: Vario Plus), and the amount of carbon dioxide in the rich liquid (i.e., absorption capacity) is determined by collecting CO2 gas, and the absorption rate is calculated, absorption rate = (amount of carbon dioxide before absorption - amount of carbon dioxide after absorption) / carbon dioxide content in flue gas × 100%. The test results are shown in Table 1.
[0064] Desorption: The rich liquid obtained from the rich liquid tank of the absorption tower is preheated to 80°C through a heat exchanger and sprayed from the top of the desorption tower. There is a heat exchange device heated by steam at the bottom of the desorption tower. The rich liquid that absorbs carbon dioxide is partially desorbed in the desorption tower and heated to 105°C in the heat exchange device for desorption again. The desorbed liquid flows into the bottom of the desorption device. The high-temperature desorbed gas and water vapor are discharged from the top of the desorption tower and then enter the condenser and vapor-liquid separator. The condensed water cooled and separated in the desorbed gas returns to the desorption tower to obtain a relatively pure high-temperature CO2 gas and send it to the next process. The high-temperature desorption gas transfers heat to the rich liquid sprayed from the top, which can heat the 85°C rich liquid and make it easy to desorb. The rich liquid after desorption is called lean liquid, which is discharged from the bottom of the desorption tower into the lean liquid tank and recycled as a flue gas decarbonizer. After the flue gas decarbonization is completed, the obtained decarbonized rich liquid is placed in a three-necked flask, one of which is inserted with a thermometer, and the other is inserted with a flue gas pipe leading to the bottom of the decarbonized rich liquid. Nitrogen is introduced into the flue gas pipe at a rate of 2×10 -4 Nm 3 / min, the time of introduction is 80 minutes, and the absorbed carbon dioxide is heated to 100℃ at the same time to desorb the absorbed carbon dioxide to obtain lean liquid. The amount of carbon dioxide remaining in the lean liquid is determined by collecting CO2 gas, and the desorption rate is calculated. The desorption rate = (the amount of carbon dioxide before desorption - the amount of carbon dioxide after desorption) / the amount of carbon dioxide before desorption × 100%. The test results are shown in Table 1.
[0065] Corrosion inhibition test: 400 mL of the energy-saving corrosion inhibition decarbonizer solution prepared in Examples 1-3 and Comparative Examples 6-8 were taken respectively, the solution temperature was 80°C, and a full immersion test was performed using an A3 carbon steel standard test piece. The reaction time was 336 h (14 d), and the weight of the A3 test piece before and after the reaction was measured, and the corrosion rate of different flue gas decarbonizer solutions was calculated. The test results are shown in Table 2.
[0066] Table 1 Absorption capacity test results
[0067]
[0068] As shown in Table 1, the absorption rate of the energy-saving corrosion-inhibiting decarbonizer prepared by the present invention is above 95%, and the highest can reach 98.9%. The desorption rate is above 85%, and the highest can reach 92.4%. The regeneration heat consumption is 1098-1215 kJ / Nm 3 CO2, which fully demonstrates that the energy-saving corrosion-inhibiting decarburizer prepared by the preparation method of the energy-saving corrosion-inhibiting decarburizer provided by the present invention has the characteristics of high purification degree, large absorption capacity, fast absorption speed, large desorption rate and low regeneration energy consumption. Among them, the energy-saving corrosion-inhibiting decarburizer prepared in Example 3 has the best performance in all aspects and is the best embodiment of the present invention.
[0069] Compared with Example 3, Comparative Example 1 uses an equal amount of anhydrous ethanol instead of 1,3-propane sultone, but the absorption rate of the obtained decarbonizing agent is reduced, and the regeneration energy consumption is increased. Comparative Example 2 uses an equal amount of alkyl dimethyl sulfopropyl betaine instead of 1,3-propane sultone, but the absorption rate of the obtained decarbonizing agent is reduced, and the regeneration energy consumption is increased, which fully demonstrates that 1,3-propane sultone can effectively increase the absorption amount and absorption rate of carbon dioxide by N-methyldiethanolamine, and reduce the regeneration energy consumption; Comparative Examples 3 to Comparative Examples 5 change the components or dosage ratios of the activators, but the absorption rate and desorption rate of the obtained decarbonizing agents are reduced to varying degrees, and the regeneration energy consumption is increased, which demonstrates that 2-amino-2-methyl-1-propanol and ethanolamine in the present invention have a synergistic effect, achieving an effect of 1+1>2.
[0070] Table 2 Corrosion inhibition effect test
[0071]
[0072] As can be seen from Table 2, the energy-saving corrosion-inhibiting decarbonizer solution provided by the present invention has a low corrosion rate on metal equipment and has a good slow-release effect. Compared with Example 3, Comparative Examples 6 to 8 changed the components or dosage of the corrosion inhibitor, but the corrosion rate of the prepared decarbonizer solution on the metal increased to varying degrees, which shows that the corrosion inhibitor provided by the present invention has been optimized, and changing the components or dosage of the corrosion inhibitor will reduce the corrosion inhibition effect.
[0073] The above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any person skilled in the art shall not modify the above embodiments without violating the spirit and scope of the present invention. Therefore, any modification, equivalent substitution and improvement made by those skilled in the art under the technical concept of the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing an energy-saving corrosion-inhibiting decarbonizer, characterized in that: The steps include: S1: Ethylene carbonate, catalyst and anhydrous ethanol are mixed and added into a reaction kettle, methylamine solution is added dropwise after heating, the mixture is kept warm for reaction, and cooled to obtain a main absorbent solution; S2: dissolving 1,3-propane sultone in anhydrous ethanol and mixing them evenly to obtain solution A; then adding solution A dropwise to the main absorbent solution obtained in step S1 under room temperature and stirring, and reacting at the same temperature to obtain a modified absorbent solution; S3: adding an activator, a corrosion inhibitor and boric acid to the modified absorbent solution obtained in step S2, stirring evenly, to obtain an energy-saving corrosion-inhibiting decarbonizer; The activator in step S3 is composed of 2-amino-2-methyl-1-propanol and ethanolamine in a mass ratio of 4-8:3-5.
2. The method for preparing the energy-saving corrosion-inhibiting decarbonizer according to claim 1, characterized in that: The mass proportions of the ethylene carbonate, catalyst and methylamine solution in step S1 are: 40-50 parts of ethylene carbonate, 5-8 parts of catalyst and 20-30 parts of methylamine solution.
3. The method for preparing the energy-saving corrosion-inhibiting decarbonizer according to claim 1, characterized in that: The catalyst in step S1 is one of strong basic styrene type I anion exchange resin, strong basic styrene type II anion exchange resin and 717 anion exchange resin.
4. The method for preparing the energy-saving corrosion-inhibiting decarbonizer according to claim 1, characterized in that: The mass percentage of the methylamine solution in step S1 is 40%-45%, and the dropping speed of the methylamine solution is 0.32-0.43 mL / min.
5. The method for preparing the energy-saving corrosion-inhibiting decarbonizer according to claim 1, characterized in that: The heating temperature in step S1 is 115-130° C., and the insulation reaction time is 2-2.5 hours.
6. The method for preparing the energy-saving corrosion-inhibiting decarbonizer according to claim 1, characterized in that: The amount of 1,3-propane sultone used in step S2 is 0.8-1.2 times the mass of ethylene carbonate.
7. The method for preparing the energy-saving corrosion-inhibiting decarbonizer according to claim 1, characterized in that: The dropwise addition rate of the solution A in step S2 is 0.5-0.7 mL / min.
8. The method for preparing the energy-saving corrosion-inhibiting decarbonizer according to claim 1, characterized in that: The corrosion inhibitor in step S3 is composed of N-methyl-1-hexadecylamine and 2-methylbenzothiazole in a mass ratio of 11-14:7-9.
9. The method for preparing the energy-saving corrosion-inhibiting decarbonizer according to claim 1, characterized in that: In step S3, the mass fraction of the corrosion inhibitor is 20-25 parts, the mass fraction of the activator is 10-15 parts, and the mass fraction of the boric acid is 10-15 parts.
Citation Information
Patent Citations
Technology of carbon dioxide removal from reaction recycle gas of vinyl acetate monomer
CN102641653A
Method for removing carbon dioxide in high-purity gas
CN114522504A
CO2 absorbing solution
CN105498449A